FLEXING DAN PERSONAL BRANDING: KONTEN ANALISIS SOSIAL MEDIA GENERASI Z DI INDONESIA - Ai Nurul Fahmi; Siti Komariah; Puspita Wulandari (UNIVERSITAS SEBELAS MARET (UNS), 2024)
Generation Z's flexing and personal branding practices on social media that display wealth, achievements, appearance, and relationships attract public attention. This qualitative study with a virtual ethnography research design aims to identify the behavioral patterns of generation Z in interacting on social media as well as the perceptions of the viewing audience. Data was collected through observations on influencers' social media accounts and Twitter using the keywords 'flexing' and 'personal branding' and interviews with 6 informants. Data that met the criteria was then interpreted contextually and recontextually until it entered the content analysis stage. The results were analyzed using symbolic interactionism theory, social reality construction theory, and critical theory. As a result, Generation Z's behavior patterns in flexing or personal branding have characteristics that describe symbols of wealth, achievement, appearance, and relationships. This forms a social reality about the standard of living reflected in social media. The negative impact affects the emergence of alienation, social inequality, and exploitation.